AMPK signalling: Implications for podocyte biology in diabetic nephropathy. (21st February 2019) - Szrejder, Maria; Piwkowska, Agnieszka
Abstract: Diabetic nephropathy is a major long‐term complication of diabetes mellitus and one of the most common causes of end‐stage renal disease. Thickening of the glomerular basement membrane, glomerular cell hypertrophy and podocyte loss are among the main pathological changes that occur during diabetic nephropathy, resulting in proteinuria. Injury to podocytes, which are a crucial component of the glomerular filtration barrier, seems to play a key role in the development of diabetic nephropathy. Recent studies have suggested that dysregulation of AMP‐activated kinase protein, which is an essential cellular energy sensor, may play a fundamental role in this process. The purpose of this review is to highlight the molecular mechanisms associated with AMP‐activated protein kinase (AMPK) in podocytes that are involved in the pathogenesis of diabetic nephropathy. Abstract : Review : Podocytes constitute the final barrier to protein leakage, and podocyte injury is considered to play a central role in the development of glomerular diseases. The morphological features of diabetic nephropathy correlate with decreased AMP‐activated protein kinase (AMPK) activity and dysregulated signalling. Impaired AMPK function causes abnormal lipid and glucose metabolism, insulin resistance, oxidative imbalance and excessive protein synthesis, leading to apoptosis, hypertrophic podocytes and loss of selective filtering by the glomerulus (albuminuria). AMPK stimulation reverses these changes, attenuating diabetes‐induced renal damage and proteinuria (Figure 5).